PENGARUH LATIHAN ATTACK AND RETREAT DRIIL TERHADAP KELINCAHAN PADA ATLET BOLABASKET SMA NEGERI 6 PEKANBARU - Mayra Wahyuni Wahyuni; Slamet '; Ardiah Juita Juita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract:Problem in this study,type this study there kind of an experiment. thet agility basketball SMA negeri 6 pekanbaru country still lacking good, in can be seen from the exercise will be undertaken even in the game, at which time the ball dribbbling often loose and often in grab opponents.purpose of this study is to look at the effects of exercise on the attack and retrea agility drills in basketball athletes SMA Negeri 6 pekanbaru. This type of research is all the exsperiments to see the effect of exercise in the study population is a basketball athlete SMA Negeri 6 prkanbaru that total 12 people. Sampling technique that the total sampling, which means that the entire population sampled is then in this study sampel were 12 people. Instument in this study using the illinois agility test run see agility. Analysis was perfomed using t-test. Based on the analysis of the data with the discussion, it can be concluded that there are significant atteck and retreat practice agility drill for basketball athetes SMA Negeri 6 pekanbaru country as evidenced by the thitung 8.595 > ttabel 1.796 pada α=0,05. Keywords:Attack And Retreat Driil, agility